Reductions in skeletal muscle mitochondrial mass are not restored following exercise training in patients with chronic kidney disease. Issue 1 (6th December 2019) - Watson, Emma L.; Baker, Luke A.; Wilkinson, Thomas J.; Gould, Douglas W.; Graham‐Brown, Matthew P.M.; Major, Rupert W.; Ashford, Robert U.; Philp, Andrew; Smith, Alice C.
Abstract: Patients with chronic kidney disease (CKD) exhibit reduced exercise capacity, poor physical function and symptoms of fatigue. The mechanisms that contribute to this are not clearly defined but may involve reductions in mitochondrial function, mass and biogenesis. Here we report on the effect of non‐dialysis dependent CKD (NDD‐CKD) on mitochondrial mass and basal expression of transcription factors involved in mitochondrial biogenesis compared to a healthy control cohort (HC). In addition, we sought to investigate the effect of a 12‐week exercise‐training programme on these aspects of mitochondrial dysfunction in a NDD‐CKD cohort.For the comparison between NDD‐CKD and HC populations, skeletal muscle biopsies were collected from the vastus lateralis (VL) of n=16 non‐dialysis dependent CKD patient's stage 3b‐5 (NDD‐CKD) and n=16 healthy controls matched for age, gender and physical activity (HC). To investigate the effect of exercise training, VL biopsies were collected from n=17 NDD‐CKD patients before and after a 12‐week exercise intervention that was comprised of aerobic exercise (AE) or a combination of aerobic exercise and resistance training (CE). Mitochondrial mass was analysed by citrate synthase activity and mitochondrial protein content by Porin expression, whilst the expression of transcription factors involved in mitochondrial biogenesis were quantified by real‐time qPCR. NDD‐CKD patients exhibited a significant reduction in mitochondrial mass when compared to HC, coupled to a reduction in PGC‐1α, NRF‐1, Nrf2, TFam, mfn2 and SOD1/2 gene expression. 12‐weeks of exercise training resulted in a significant increase in PGC‐1α expression in both groups, with no further changes seen across indicators of mitochondrial biogenesis. No significant changes in mitochondrial mass were observed in response to either exercise programme. NDD‐CKD patients exhibit reduced skeletal muscle mitochondrial mass and gene expression of transcription factors involved in mitochondrial biogenesis compared to HC. These reductions were not restored following 12‐weeks of exercise training implying exercise resistance in this cohort. The reasons for this lack of improvement are currently unknown and require further investigation, as reversing the dysregulation of these processes in NDD‐CKD may provide a therapeutic opportunity to improve muscle fatigue and dysfunction in this population.